2008
DOI: 10.2225/vol11-issue5-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in Venezuelan rice cultivars using simple sequence repeats markers

Abstract: In Venezuela, pedigree analyses indicate that the rice varieties currently under cultivation are closely related. Effective breeding programs, based on knowledge of the genetic diversity of cultivars, are needed to broaden the genetic bases of rice germplasm in the country. In this study, we used a set of 48 simple-sequence-repeat (SSR) markers to assess the genetic diversity of 11 Venezuelan rice cultivars, released by the National Rice Breeding Program between 1978 and 2007. A total of 203 alleles were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 54 publications
6
6
0
1
Order By: Relevance
“…Nei's gene diversity, which varied from 0.16 for check accessions to 0.58 for Sabah varieties with an average value of 0.36, also indicated the high level of divergence in the population. This value aligned with that of [39], which reported mean Nei's gene diversity of 0.37 but lower than 0.50 [40]. …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Nei's gene diversity, which varied from 0.16 for check accessions to 0.58 for Sabah varieties with an average value of 0.36, also indicated the high level of divergence in the population. This value aligned with that of [39], which reported mean Nei's gene diversity of 0.37 but lower than 0.50 [40]. …”
Section: Resultssupporting
confidence: 87%
“…In another study, three distinct clusters were also found from 18 rice cultivars studied using 44 SSR markers [39]. The clustering patterns in the current study gave some consideration to the geographical origin of the populations.…”
Section: Resultssupporting
confidence: 57%
“…The average gene diversity index was considerably high (0.90) (Table 4), indicating its relevance to previous reports that used similar universal SSR markers and displayed moderate to high variability in mutants (Tembo and Munyinda 2015;Yuliasti and Reflinur 2017). In addition, this study was in good agreement with previous report from Herrera et al (2008), that gene diversity of each SSR locus was correlated with the number of alleles and number of repeat motifs. Heterozygosity was also identified in a number of SSR loci in these mutants, suggesting the segregated soybean mutant lines observed in this study.…”
Section: Molecular Diversity Among Soybean Mutantssupporting
confidence: 91%
“…Screening and identification of highly tolerant donors for seedling stage cold tolerance from the germplasm pool is an important step for selection of donor parents in cold tolerance breeding program. Molecular markers, usually SSR or Simple Sequence Length Polymorphism (SSLP) are commonly being used for assessing rice genetic diversity (Panaud et al, 1996; Wu and Tanksley, 1996; Xiao et al, 1996; Olufowote et al, 1997; Thanh et al, 1999; Herrera et al, 2008; Pervaiz et al, 2010; Das et al, 2013; Babu et al, 2014; Anandan et al, 2016; Pradhan et al, 2016). Hence, genetic diversity available in parental lines should be assessed by using the trait linked SSRs and gene specific markers for seedling stage chilling stress tolerance before selection of parental lines.…”
Section: Introductionmentioning
confidence: 99%